Driving Performance of Depressed Patients who are Untreated or Receive Long-Term Antidepressant (SSRI/SNRI) Treatment - van der Sluiszen, Nick N. J. J. M.; Wingen, Marleen; Vermeeren, Annemiek; Vinckenbosch, Frederick; Jongen, Stefan; Ramaekers, Johannes G. (Pharmacopsychiatry, 2017)
Introduction Depression is a mental disorder likely to affect everyday functions. The present study aimed to assess actual driving performance of depressed patients who were without specific antidepressant treatment or received long-term antidepressant treatment.Methods A standardized on-the-road driving test was used to assess standard deviation of lateral position (SDLP) in 3 patient groups receiving either no antidepressant treatment (with or without benzodiazepine medication) or treatment with selective serotonin/noradrenalin reuptake inhibitors for a period of 6–52 weeks. Severity of depression was assessed using Beck’s Depression Inventory and the Hamilton Depression Rating Scale. The performance of patient groups was compared to healthy controls.Results The mean SDLP of untreated and treated patients was significantly higher than that of healthy controls. Driving impairment in the long-term treated group was significantly less than in the untreated groups. SDLP was positively correlated to severity of depression across all groups.Discussion It is concluded that symptoms of depression are a major cause of driving impairment. Reductions in severity of depression through antidepressant treatment reduce severity of driving impairment.
Keywords: antidepressants; depression; driving performance; long-term treatment